2023
DOI: 10.1002/jmv.29144
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive PCR system for HBV DNA detection: Risk stratification for occult hepatitis B virus infection in English blood donors

Michael X. Fu,
Peter Simmonds,
Julien Andreani
et al.

Abstract: Occult hepatitis B (HBV) infection (OBI), characterized by low viral loads, accounts for much of the risk of HBV transfusion‐transmitted infection. With anticore antibodies (anti‐HBc) screening introduced in England, the imperative to identify OBI donors has increased. We aimed to develop an ultra‐sensitive PCR system and investigate risk factors for HBV DNA presence in blood donations. Seven extraction methods and three PCR assays were compared. The optimal system was sought to determine HBV DNA presence in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…We recently showed that a higher anti-HBc titre was predictive of DNA presence in the plasma of anti-HBc positive donors, 44 corroborating other findings that higher anti-HBc levels were independently associated with detecting cccDNA. 52 Increased anti-HBc levels suggest the production of more HBV core antigens and may correlate with increased production of infectious virions, translating to higher TTI risk.…”
Section: Hepatitis B Virus Dnasupporting
confidence: 84%
See 4 more Smart Citations
“…We recently showed that a higher anti-HBc titre was predictive of DNA presence in the plasma of anti-HBc positive donors, 44 corroborating other findings that higher anti-HBc levels were independently associated with detecting cccDNA. 52 Increased anti-HBc levels suggest the production of more HBV core antigens and may correlate with increased production of infectious virions, translating to higher TTI risk.…”
Section: Hepatitis B Virus Dnasupporting
confidence: 84%
“…43 We recently developed an ultrasensitive HBV DNA Polymerase chain reaction (PCR) system with a 50% LOD of 0.12 IU/mL, where assay sensitivity was improved by increasing sample representation and extraction volume to 5 mL of plasma. 44 Indeed, testing DNA extracts from at least 1 mL of sample was also previously recommended. 3 Increasing the sample volume in automated testing in diagnostic services would significantly improve the sensitivity of HBV DNA detection, enabling further DNA-positive OBI donors to be identified.…”
Section: Hepatitis B Virus Dnamentioning
confidence: 99%
See 3 more Smart Citations